From Conflictual to Peaceful Coexistence? Reconceptualizing The Relationship between Islam and The West - Muhammad Khoirul Muqtafa (Institut Kewarganegaraan Indonesia, 2024)
The relationship between Islam and the West has been a subject of study for many scholars, yet the discussion seems never to end. Part of the reason is that their relationship is anything but simple as the historical records depict it: there was a period of tension, conflict and cooperation. The September 11 attack was critical since then the discussion between the two has been publicly discussed with the question of Islam, whether it would bring peace or instead, it would be a threat to the Western world. Employing desk research, this paper expands the discussion between Islam and the West by examining different ideas among Muslim scholars, from liberal to conservative or fundamentalist ones to see the prospect of promoting peaceful coexistence between the two. More than that, the progressive idea needs to be creatively spread and infused into the people’s consciousness so that the concept of peaceful coexistence would not only be the concern of elites but also that of the general public. Bringing this into view may shed some light to what extent the relationship between the two might be reconceptualized and proposed into a more peaceful one.